Independent freestanding emergency departments and implications for the rural emergency physician workforce in Texas - Luo, Qian (Health Serv Res, 2020)
OBJECTIVE: Independent freestanding emergency departments (IFEDs) have proliferated over the last decade, largely in Texas. We examined the IFED physician workforce composition and changes in emergency physician workforce supply across states and in rural Texas over the period of IFED proliferation following a 2009 legislation allowing the licensing of these sites. DATA SOURCES: IFED websites, Texas Medical Board lookup tool, National Plan & Provider Enumeration System (NPPES), Provider Enrollment and Chain/Ownership System (PECOS), Medicare Physician Shared Patient Patterns, CareSet DocGraph Hop Teaming, Healthcare Provider Database. STUDY DESIGN: Descriptive analysis of the IFED physician workforce; quasi‐experimental difference‐in‐difference analysis of Texas emergency physician movement into and out of the state; and difference‐in‐difference‐in‐difference analysis of the change in emergency physician supply between rural and urban areas in Texas compared with other states. DATA EXTRACTION METHODS: Using the NPIs obtained through Texas IFED websites and Texas Medical Board data, we examined NPPES/PECOS files, Medicare Physician Shared Patient Patterns, and CareSet DocGraph Hop Teaming for IFED physician practice locations from 2009 to 2017. We extracted all active emergency physicians from a Healthcare Provider Database, derived from a 5% Medicare claims (1999‐2017). PRINCIPAL FINDINGS: In 2019, 545 physicians practiced in Texas IFEDs, of which 515 (94.5%) were emergency physicians. We located 533 in previous practice, of whom 522 (97.9%) previously practiced in Disproportionate Share Hospitals and 100 (18.8%) in rural areas. Following legislation to begin licensing IFEDs in 2009, there were on average 42.1 (P < .01) moving into Texas and 17.0 (P < .01) fewer moving out compared with all other states. Our results also indicated that the difference in emergency physician supply between rural and urban Texas was 1,002 (P < .01) fewer than for other states. CONCLUSIONS: New models of health care organizations such as IFEDs have workforce implications that may further exacerbate rural and underserved workforce and access challenges.